ChemInform Abstract: Structure and Vibrational Analyses of LiP15. Issue 52 (29th December 2014) - Eckstein, Nadine; Jantke, Laura‐Alice; Faessler, Thomas F.; Mink, Janos; Drees, Markus; Nilges, Tom
Abstract The title compound is synthesized from a stoichiometric mixture of the elements in the presence of CuCl2 as a mineralizer (silica ampule, 823 K, 7 d).